FORUMS IN PHYSICS IN THE INITIAL TRAINING OF LICENSED IN EDUCATION- BIOLOGY - Torres-Rivera, Rosalina Caridad (2020)
One of the computer applications used internationally is the interactive platform Moodle for being open source and free distribution. The research presented aims to focus on the problem of rejection by Physics in 1st year students of the Regular Day Course of the Bachelor of Education-Biology career, at the Faculty of Secondary Education of the Central University "Marta Abreu" of Las Villas, Cuba, which is why the forums were used from the virtual learning environment, developed on the Moodle platform in the subject "Physics Topics" during the academic years 2017-2020, in support of the teaching-learning process of the subject in the face-to-face mode. In the research carried out, various theoretical and empirical methods were used. To collect the information, participant observation, analysis of testimonies, discussion and refl ection groups, evaluation records, in-depth interviews, and a diary were used, as well as methods of processing the information collected, both intellectual and statistical. The forums prepared were subjected to evaluation by expert criteria. The information obtained was analyzed following the triangulation process, which showed that the forums had a favorable impact on the students' results in their learning and on the increase in motivation for the subject. The use of forums reveals novel results that provide solutions from different angles, particularly the virtual classroom. Keywords: virtual classroom – virtual learning environments – forum – Moodle interactive platform – Physics